2012
DOI: 10.1525/auk.2011.11069
|View full text |Cite
|
Sign up to set email alerts
|

Variable resource availability when resource replenishment is constant: The coupling of predators and prey

Abstract: Although food resources are thought to limit many populations, the extent to which the population dynamics of predators and prey are coupled is rarely known. We examined a sedentary population of Red Crossbills (Loxia curvirostra L. complex) that relies on seeds in cones that accumulate in the canopy of Rocky Mountain Lodgepole Pine (Pinus contorta latifolia Engelm.). Nearly constant annual seed production and gradual weathering over many years of initially impenetrable cones in the tree canopy results in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The South Hills crossbill is one of 10 ecotypes (call types) in the North American red crossbill complex (Groth 1993;Benkman 1999;Irwin 2010); each ecotype is adapted for foraging on seeds in the cones of a single species of conifer that reliably holds seeds from fall to spring (Benkman 1993(Benkman , 2003Parchman and Benkman 2002). South Hills crossbills feed virtually exclusively on seeds in lodgepole pine cones (Benkman et al 2009(Benkman et al , 2012, which are available year-round in serotinous cones ( fig. 1).…”
Section: Natural History Of the South Hills Crossbillmentioning
confidence: 99%
See 2 more Smart Citations
“…The South Hills crossbill is one of 10 ecotypes (call types) in the North American red crossbill complex (Groth 1993;Benkman 1999;Irwin 2010); each ecotype is adapted for foraging on seeds in the cones of a single species of conifer that reliably holds seeds from fall to spring (Benkman 1993(Benkman , 2003Parchman and Benkman 2002). South Hills crossbills feed virtually exclusively on seeds in lodgepole pine cones (Benkman et al 2009(Benkman et al , 2012, which are available year-round in serotinous cones ( fig. 1).…”
Section: Natural History Of the South Hills Crossbillmentioning
confidence: 99%
“…1A, 1B). Crossbills rely on seeds in these gradually opening serotinous cones (Smith and Benkman 2007;Benkman et al 2012).…”
Section: Natural History Of the South Hills Crossbillmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows to illustrate an approach of GEI occurring at the interspecific level by considering five virtual bird species of varying adult masses in the range of 5-45 g. This was intended to generate a gradient in size in passerine species ranging from that of the Goldcrest (Regulus regulus) to that of the Red Crossbill (Loxia curvirostra). Environmental variation was simulated using five different scenarios of temperature variation obtained by translating realistic temperature series experienced by Red crossbills (Benkman et al, 2012) into a temperature delta of −2 to +2 • C. The model was run for 5 × 5 combinations of bird species and temperature values. The parameter values were taken from Benkman et al (2012), except hatching success HS that was assumed to vary with temperature whatever the species as follows: HS = HS cst + 0.1 × θ , where θ is the temperature delta mentioned above and HS cst is the value used by Benkman et al (2012).…”
Section: An Example Of Gei Occurrence In An Ecological Modelmentioning
confidence: 99%
“…Several researchers have demonstrated that selective pressure exerted by pre-dispersal seed predators on conifer species results in the confers increasing their energy investment in seed protection (e.g., Benkman, Holimon & Smith, 2001; Siepielski & Benkman, 2008; Benkman, Fetz & Talluto, 2012). The presence of pre-dispersal seed predators usually results in the coniferous species producing cones with larger and thicker scales (Benkman et al, 2003; Mezquida & Benkman, 2005).…”
Section: Introductionmentioning
confidence: 99%